RESPON BAHAN STERILAN PADA EKSPLAN JELUTUNG RAWA (Dyra lowii) - Rodinah Rodinah; Fakhrur Razie; Dina Naemah; Adistina Fitriani (Lambung Mangkurat University-Indonesia, 2016)
Jelutung is a high economic value. Nature nursery jelutung problem is recalcitran seeds. Technology in vitro give solution for the supply of seeds in large quantities. The purpose of this research is to know the effect of sterilan material with jelutung eksplan, the best strilan and eksplan material. This study used Completely Randomized Design, Two factors. First factor of sterilized material (S); S1 = 70% alcohol, bayclin 20%, H2O2 17,6%, bayclin 10%; S2 = fungicide, bactericide, alcohol 70%, H2O2 17,6%, bayclin 20%; S3 = fungicide, bactericide, alcohol 70%, sublimate 0.2%, H2O2 17.6%, bayclin 20%; S4 = fungicide, bactericide, alcohol 70%, sublimate 0.2%, H2O2 17.6%, bayclin 10: s5 = fungicide, bactericide, 70% alcohol, sublimate 0.2%, H2O2 17.6%, bayclin 20% , Bayclin 10%. Second factor eksplan (E): e1= Leaf, e2 = nude. The research results obtained the smallest percentage of contamination on leaves and nudes on S5. The smallest percentage of browsed on S1 The highest percentage of live on S1. The smallest percentage of contamination on the leaves, while the lowest percentage browning on the nude and the highest live percentage on leaf explants.Jelutung merupakan tanaman bernilai ekonomis tinggi. Pembibitan jelutung terkendala sifat benih recalcitran. Teknologi secara in vitro guna penyediaan bibit dalam jumlah banyak. Tujuan penelitian ini untuk mengetahui pengaruh bahan sterilan dengan eksplan jelutung dan bahan strilan dan eksplan yang terbaik. Penelitian ini menggunakan Rancangan Acak Lengkap, dua faktor. Faktor pertama bahan sterilan (S); s1 = alkohol 70 %, bayclin 20 %, H2O2 17,6 %, bayclin 10 % ; s2 = fungisida, bakterisida, alkohol 70 %, H2O2 17,6 %, bayclin 20 % ; s3 = fungisida, bakterisida, alkohol 70 %, sublimat 0,2 %, H2O2 17,6 %,bayclin 20 %; s4 = fungisida, bakterisida, alkohol 70 %, sublimat 0,2 %, H2O2 17,6 %,bayclin 10 : s5 = fungisida, bakterisida, alkohol 70 %, sublimat 0,2 %, H2O2 17,6 %, bayclin 20% ,bayclin 10 %. Faktor kedua eksplan (E) : e1 = daun, e2 = buku. Hasil penelitian memperoleh persentase kontaminasi terkecil pada daun dan buku pada s5. Persentase browning terkecil didaun pada s1 Persentase hidup tertinggi pada s1. Persentase kontaminasi terkecil pada daun, sedangkan persentase browning terendah pada buku dan persentase hidup yang tertinggi pada eksplan daun.